PROCESS OPTIMIZATION OF DATA TRANSMISSION BETWEEN THE SYSTEM, DEVELOPED ON THE PLATFORM 1C: ENTERPRISE 8 - Литвинов, В.В.; Дмитраш, О.В.; Хоменко, А.В. (Science-based technologies, 2009)
In this article existent methods are described transmissions given between the systems developed on the platform of 1С: Enterprise  8(system of 1С). Today every enterprise must conduct a tax, administrative, book-keeping ac-counts (a lot of enterprises give advantage the systems of 1С, which are remarkably adapted under our tax sys-tem). With stormy development the Internet an own site it a not luxury, but necessity. Very comfortably to be in a position to execute an exchange information between the system of 1С and web-site. Optimization transmissions given is the matter of great importance.